2010
DOI: 10.2903/j.efsa.2010.1649
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the re-evaluation of Amaranth (E 123) as a food additive

Abstract: The Panel on Food Additives and Nutrient Sources added to Food provides a scientific opinion re-evaluating the safety of Amaranth (E 123). Amaranth has been previously evaluated by JECFA in 1972, and the SCF in 1976. In 1984 the SCF set an ADI for Amaranth of 0-0.8 mg/kg bw/day based on results from a 90-day rat study. In contrast, in 1984 JECFA allocated an ADI of 0-0.5 mg/kg bw/day Amaranth based on a long-term carcinogenicity study in rats. In evaluating the overall toxicological database on Amaranth, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The two isolated compounds are being referred to EFSA as amaranth (E123) and azorubine or carmoisine (Ε122) and are well-known food dyes [19, 23]. …”
Section: Resultsmentioning
confidence: 99%
“…The two isolated compounds are being referred to EFSA as amaranth (E123) and azorubine or carmoisine (Ε122) and are well-known food dyes [19, 23]. …”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that the intake for Quinoline Yellow (E104) at the maximum levels of use of with refined (Tier 2 and Tier 3) intake estimates are generally well over the ADI of 0.5 mg/kg bw/day (EFSA, 2009b). For E110 and E123 European Adult populations are below the ADI (EFSA, 2011a(EFSA, , 2010c(EFSA, , 2013b. The EFSA Panel concluded for Ponceau 4R (E124) that at the maximum levels of use, intake estimates for adults (P97.5) and for 1-to 10-year old children (mean and P97.5) were generally above the ADI even in the refined intake estimates (EFSA, 2009a).…”
Section: Tier 2 and Refined Tier 2 Exposure Assessmentmentioning
confidence: 98%
“…Ponceau 4R-also known as "cochineal red A", "Cl food red 7" or "new coccine"-is a synthetic azo food colouring (E124) that gives a red colour to foodstuffs. This food colour (1-(4-sulfo-1-napthylazo)-2-napthol-6,8-disulfonic acid, trisodium salt) is a reddish powder or granule which is soluble in water and sparingly soluble in ethanol [115]. This colourant is manufactured by coupling diazotized naphthionic acid to G acid (2-naphthol-6,8-disulfonic acid), followed by the conversion of the coupling product to the trisodium salt.…”
Section: Ponceau 4rmentioning
confidence: 99%